Changes in Urinary Microbiome Populations Correlate in Kidney Transplants With Interstitial Fibrosis and Tubular Atrophy Documented in Early Surveillance Biopsies. Issue 3 (11th October 2016) - Modena, B. D.; Milam, R.; Harrison, F.; Cheeseman, J. A.; Abecassis, M. M.; Friedewald, J. J.; Kirk, A. D.; Salomon, D. R.
Abstract : An unbalanced microbiome may lead to disease by creating aberrant immune responses. A recent association of cellular rejection with the development of interstitial fibrosis and tubular atrophy (IFTA) suggests the role of immune‐mediated tissue injury. We hypothesized that developing IFTA correlates with altered urinary tract microbiomes (UMBs). UMBs at two serial time points, 1 and 6–8 months posttransplant, were assessed by 16S microbial ribosomal gene sequencing in 25 patients developing biopsy‐proven IFTA compared to 23 transplant patients with normal biopsies and excellent function (TX) and 20 healthy nontransplant controls (HC). Streptococcus, the dominant genera in HC males, was lower in IFTA and TX males at 1 month compared to HCs. At 6–8 months, Streptococcus was further decreased in IFTA males, but normalized in TX. IFTA males and females had increases in number of genera per sample at 6–8 months. UMB composition varied substantially between individuals in all groups. Despite the wide variation in UMBs between individuals, IFTA was associated with a loss in dominant resident urinary microbes in males, and a parallel increase in nonresident, pathogenic bacteria in males and females. UMB changes may contribute to IFTA development by alteration of the host immune response. Abstract : The authors assess urinary microbiomes at 1 and 6–8 months posttransplant in 25 patients who developed biopsy‐proven interstitial fibrosis and tubular atrophy (IFTA), 23 transplant patients with normal biopsies and excellent function, and 20 healthy controls, and find an association of the development of IFTA with a loss in dominant resident urinary microbes in males, and a parallel increase in nonresident, pathogenic bacteria in males and females.